Mathematical Modelling Of Backward Extraction Mixed Reverse Micelle Of Amoxicillin By Surface Response Methodology (RSM) - Siti Norazimah, Mohamad Aziz; Mimi Sakinah, A. M. (Universiti Malaysia Pahang, 2017)
One of important factor in reverse micelle extraction is backward transfer. It is important to investigate the favourable conditions for backward transfer from reverse micellar phase to an organic phase. The back extraction of amoxicillin was studied using mixed reverse micelle with combination sodium bis(2-ethylhexyl) sulfosuccinate (AOT) and TWEEN 85. Backward extraction was optimized via response surface methodology (RSM). For mathematical modelling, Central Composite Design (CCD) was used to studies the significant of independent variables: pH of stripping solution (5-8), KCl concentration (2.0 -16.0 g/L) and backward extraction time (5-35 minutes) on the response of the process. Optimized backward extraction for maximized final mass of amoxicillin extracted into aqueous were pH of stripping solution (6.58), backward time (19.8 minutes) and concentration of KCl (11.02 g/L) on the response of the process. Result showed that the experimental data was fitted well to a second-order polynomial model.